Case report on Ewing's sarcoma with review of literature - Agrawal, Sonam; Rathod, Vanita C; Agrawal, Pankaj Kumar; Saluja, Swati (Asian Journal of Medical Sciences, 2015)
Ewings sarcoma is a highly malignant primary mesenchymal neoplasm of bone,which was first reported in 1921 by Ewing. The exact cell of origin of Ewing Sarcoma is not known it is generally believed that the lesion arises from either the endothelial cells of the blood vessels within the bone or from the undifferentiated reticulo-endothelial cell. Primitive neuroectodermal tumors (PNETs) arises from mesenchymal stem cells that differentiates along neural cell lineage. Reports of Ewings sarcoma constitute about 10% of all malignant bone tumor. A case of Ewings sarcoma in 10 year old male patient is reported, who visited to Dept of Oral and Maxillo-facial Pathology in Rungta College of Dental Sciences And Research, with chief complaint of pain and swelling in right side of face since 1 month. Early diagnosis of this case helps in selecting the appropriate treatment procedure and to avoid further complication. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12283 Asian Journal of Medical Sciences Vol.6(6) 2015 88-92